18F-PSMA-1007 PET in Biochemical Recurrent Prostate Cancer: An Updated Meta-Analysis. (18th December 2021) - Ferrari, Matteo; Treglia, Giorgio
Abstract : Background . Prostate-specific membrane antigen- (PSMA-) targeted agents labeled with fluorine-18 ( 18 F) have recently become available to evaluate patients with biochemical recurrent prostate cancer (BRPCa) by using positron emission tomography/computed tomography (PET/CT) or positron emission tomography/magnetic resonance imaging (PET/MRI). We performed a systematic review and meta-analysis about the detection rate (DR) of 18 F-PSMA-1007 PET/CT or PET/MRI in BRPCa patients. Methods . A comprehensive computer literature search of PubMed/MEDLINE, EMBASE, and Cochrane Library databases for studies published through 17 May 2021 was carried out using the following search algorithm: "PSMA" AND "1007". Only studies providing data on the DR of 18 F-PSMA-1007 PET/CT or PET/MRI in BRPCa were included. A random-effects model was used to calculate the pooled DR on a per scan basis. Results . Fifteen articles (853 patients) were selected and included in the systematic review, and ten were included in the quantitative analysis. Most of the studies reported a good DR of 18 F-PSMA-1007 PET/CT or PET/MRI in BRPCa including also patients with low prostate-specific membrane antigen (PSA) values. The DR of 18 F-PSMA-1007 PET/CT or PET/MRI was dependent on PSA serum values. The pooled DR was 81.3% (95% confidence interval: 74.6–88%) with statistical heterogeneity. A significant reporting bias (publication bias) was not detected. Conclusions . 18 F-PSMA-1007 PET/CT or PET/MRI showed a good DR in BRPCa patients in line with other PSMA-targeted agents. The DR of 18 F-PSMA-1007 PET/CT or PET/MRI is influenced by serum PSA values. These findings should be confirmed by prospective multicentric trials.